Regulatory Preconditions for the Deployment of Bioenergy With Carbon Capture and Storage in Europe - Nehler, Therese; Fridahl, Mathias (Frontiers in Climate, 2022)
Paris-compatible climate scenarios often consider bioenergy with carbon capture and storage (BECCS) as an important technology for carbon dioxide removal (CDR). Although the main barrier to BECCS deployment is often associated with lack of economic policy incentives, unfavorable regulations can also impede investments. Over the past decade, the regulatory conditions at the UN and on the EU level have developed to be more permissive toward BECCS. For instance, CDR accounting guidelines have been developed by the UN, and the EU CCS Directive regulates responsibilities regarding storage of CO2. However, several existing regulations still cause deployment hurdles. Taking a European viewpoint, this perspectives article takes stock of recent regulatory developments and provides a discussion on legal acts that need to be reformed in order to facilitate BECCS deployment. Although the European trend is characterized by developing a regulatory regime that is more supportive of BECCS, we identify three areas for further improvement: (1) allowing EU Member States to use negative emissions from BECCS to comply with their obligations under the legislative pillars that underpin the EU's climate objectives: (2) amending the CCS Directive to exempt physical leakage of biogenic CO2, attributable to sustainably sourced biomass, from the requirement to surrender emission allowances in the EU ETS or, if BECCS has been economically rewarded, the penalty for leakage should correspond to the level of the reward; and (3) pushing to erase the last few barriers due to multilateral regimes, such as clarifying whether BECCS is covered by the geoengineering moratorium maintained by the UN Convention on Biological Diversity. These proposed reforms would further improve the regulatory preconditions for BECCS deployment in the EU.